An improved exponential EWMA chart for monitoring time between events. (17th March 2022) - Zhang, Yang; Shang, Yanfen; Hu, Xuelong; Li, An‐Da
Abstract: Many control charts have been developed for monitoring the time between adverse events (TBE) to improve the quality of processes. In practice, the decrease in the TBE mean usually implies a deterioration of the process, while the increase indicates an improvement of the process. In this paper, an improved lower‐sided EWMA control chart is developed based on the power of the TBE observations to detect the decreasing TBE mean. Furthermore, an optimization model is developed to design the proposed EWMA chart, including the determination of the power and smoothing parameters to ensure the best overall performance. Simulation studies show the proposed EWMA chart is best among several charts for monitoring small shifts, and performs better than most alternative methods in detecting moderate shifts. Moreover, the in‐control performance of the proposed method with parameter estimation is studied via many numerical simulations. Finally, a real data example is given to further illustrate the application and sensitiveness of the improved EWMA chart.